Pelayanan Administrasi Kartu Identitas Anak (KIA) Melalui Sistem Informasi Aplikasi Pelayanan (Siapel) di Dinas Kependudukan dan Pencatatan Sipil Kota Malang - Agustine, Adhinda Dewi; Hertanto, Yogi (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2024)
The research aims to explain and describe the quality and description of the implementation of children's identity card services through the electronic service application information system at the Malang City Population and Civil Registration Service. The research method used is a descriptive qualitative approach, namely a problem-solving approach that relies on descriptions without using data in the form of numbers. Data collection was carried out using interview, observation, and documentation techniques. Data analysis in this research uses 4 components consisting of data collection, data condensation, data presentation and drawing conclusions. Based on the results of the research conducted, the child identity card service through the electronic service application information system at the Malang city population and civil registration service has been running quite well. With efforts to fulfill the dimensions of public service quality, namely the tangible dimension (physical evidence), the reliability dimension (reliability), the responsiveness dimension (responsiveness), the assurance dimension (guarantee), the empathy dimension (empathy). Furthermore, the results obtained were that the supporting factors were the availability of adequate support facilities for implementing services, while the inhibiting factors were the lack of resources and lack of public understanding. Recommendations that can be considered based on the implementation of this research are the need to provide a Standard Operating Procedure (SOP) for the Electronic Service Application Information System (SIAPEL) program, increase awareness of employees or officers to be friendly and implement 5S (Smile, Greetings, Compliments, Polite and Mannerly), Carrying out training, recruiting employees and conducting scheduled outreach to the community.